Etnobotani: Potensi Tumbuhan Samauang (Pangium edule) di Lubuk Jambi, Riau - Resvi Hardianti; Desti, Desti; Febrian, Andika (MANILKARA: Journal of Bioscience, 2024)
Not much attention from the people of Lubuk Jambi, Riau to indigenous knowledge on the utilization of samauang (Pangium edule) fruit, especially its seed meat as a preservative for pet meat, has resulted in the erosion of information on the benefits of samauang fruit. This research aims to study the potential of the samauang plant as a preservative for pet meat in the community of Lubuk Jambi, Riau. The research used a qualitative method with descriptive analysis. The sampling technique used purposive sampling which was collected through observation, interviews, documentation, and literature review. The results showed that the fruit of the samauang plant, which grows in Lubuk Jambi, can be used by the community as a preservative for pet meat, so as to minimize the potential for changes in meat properties to taste stale.